In the field : a novel - Pastan, Rachel (Delphinium Books, 2021)
A novel inspired by the life of the scientist who won the Nobel Prize in 1983, follows Kate Croft who attends college in 1920 and, confused by her own sexuality, finds refuge in the rationality of biology and genetics.